The Influence of Lifestyle and Social Environment through Financial Literacy on the Financial Behavior of Civil Servants - Nabila, Sayidah; Aqidah, Nur Ariani; Hamida, Hamida; Megasari, Megasari (Journal of Economics and Social Sciences (JESS), 2025)
The financial behavior of civil servants is often influenced by lifestyle and social environment, as well as low financial literacy. This study aims to understand the relationship between these factors and financial behavior. The research used a quantitative approach with data collection techniques through questionnaires to 100 civil servant respondents, which were analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results showed that lifestyle has a significant positive effect on financial literacy and financial behavior. The social environment also contributes significantly to financial literacy and financial behavior. Financial literacy serves as a mediator that strengthens the influence of lifestyle and social environment on financial behavior. This study concludes that improving financial literacy, which is influenced by lifestyle and social environment, can improve the financial behavior of civil servants. Therefore, it is important for civil servants to adopt a more responsible lifestyle and improve access to and understanding of financial literacy.